2005
DOI: 10.3152/147154405781776355
|View full text |Cite
|
Sign up to set email alerts
|

Why do academic scientists engage in interdisciplinary research?

Abstract: : This article provides a first empirical study of the determinants of the interdisciplinarity of academic researchers production. For that purpose we measure interdisciplinarity as the diversity of their research production across scientific domains. Our evidence is based on more than nine hundred permanent researchers employed by a large French university which is ranked first among French universities in terms of Impact. Our main results are that the traditional academic career incentives do not stimulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 15 publications
1
76
1
Order By: Relevance
“…Ziman (1994) argued that this was much more likely to be the case in some disciplines than in others. Carayol and Thi (2005) found that university researchers who had co-published with an industry-based researcher increased interdisciplinary involvement. They also found that a research lab that are less reliant on recurrent funding and more on multiple channels of project funding were more involved in problem-solving and interdisciplinary research.…”
Section: The Rise Of Interdisciplinary Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Ziman (1994) argued that this was much more likely to be the case in some disciplines than in others. Carayol and Thi (2005) found that university researchers who had co-published with an industry-based researcher increased interdisciplinary involvement. They also found that a research lab that are less reliant on recurrent funding and more on multiple channels of project funding were more involved in problem-solving and interdisciplinary research.…”
Section: The Rise Of Interdisciplinary Researchmentioning
confidence: 99%
“…Hagstrom (1965) argued that applied research was inherently more interdisciplinary. However, the relationship between applied research and interdisciplinary collaboration is both supported (Carayol and Thi, 2005;van Rijnsoever and Hessels, 2011) and questioned (Schummer, 2004) in the literature. The orientation of individual researchers toward knowledge creation or application will vary, and may also impact on their propensity to become involved in interdisciplinary research.…”
Section: Measures and Variablesmentioning
confidence: 99%
“…Most likely, that does not mean that collaboration does not take place, but that the respective results are published by other journals with lower impact, or not in journals at all. The literature on interdisciplinarity provides some explanations relating to a lack of reviewers with interdisciplinary training, as well as the assumed negative possible impacts on the career options of young scientists among others (e.g., Carayol and Nguyen Thi 2005;Rylance 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These internal conflicts can impede one's ability to adequately share information, trust a team or network, and even hamper the advancement of a science program especially if knowledge is withheld as a result of such insecurities . Loss aversion (Fox & Faver, 1984;Georghiou, 1988;Sonnenwald, 2007), lack of recognition and reward (Dasgupta & David, 1994;Turpin & Garrett-Jones, 2010), concerns about achieving promotion and tenure (Carayol & Thi, 2005;Coleman, 1986;Harris, Lyon, & Clarke, 2009;Horlick-Jones & Sime, 2004;Maglaughlin & Sonnenwald, 2005;Rhoten & Parker, 2004;Zucker, 2012), and authorship embattlements (Barrett, Funk, & Macrina, 2005;Lewis, Ross, & Holden, 2012;Stokols et al, 2008) are just a few of the issues that can ensue from within a scientific team that struggles with diverse attitudes about knowledge sharing.…”
Section: Attitudes About Ownership Of Knowledgementioning
confidence: 99%